PENGELUARAN PEMERINTAH DAN INDEKS PEMBANGUNAN MANUSIA (IPM) DI PROVINSI BENGKULU - Aan Zulyanto (FEB Universitas Sultan Ageng Tirtayasa, 2016)
ABSTRACTHuman Development Index (HDI) is an indicator to evaluate the government performance. This index is consisting of several main components such as; education, health, and economy. This study aim is to analize the influence ofgovernment spending on education, health, and infrastructure to Human Development Index in the province of Bengkulu. In addition, this study also analyzes the differences of HDI level in the main regions and proliferationregions as a response to regional autonomy in Indonesia. This study uses panel data collected from any regencies and municipalities in Bengkulu province during the period of 2007-2013, which is Random Effect Model (GLS) be used as estimation technique. The study results show that education spending has significant and positive influence to HDI, meaning that substantial budget allocations for education can improve HDI in Bengkulu province. On theother hand, the influence of health spending and infrastructure spending show not significant and have negative relationship with HDI. The reason because there is inefficiency and inaccuracy targets of the health budget andinfrastructure in Bengkulu province. Meanwhile, the study also finds a significant difference in the level of HDI among main regions and proliferation regions, where is the main regions have higher HDI levels than the expansion regions.Key Words: Education, Government Expenditure, HDI, Health, Infrastructure.AbstrakIndeks Pembangunan Manusia (IPM) adalah sebuah indikator untuk mengevaluasi kinerja pemerintah. Indeks ini terdiri dari beberapa komponen utama, seperti pendidikan, kesehatan, dan ekonomi. Tujuan dari penelitian ini adalah untuk menganalisa pengaruh dari belanja pemerintah, kesehatan, dan infrastruktur terhadap Indeks Pembangunan Manusia di provinsi Bengkulu. Sebagai tambahan, penelitian ini juga menganalisis perbedaan antara tingkat IPM di daerah utama dan daerah pemekaran, sebagai respon dari adanya otonomi daerah di Indonesia. Penelitian ini menggunakan data panel yang didapatkan dari berbagai kabupaten dan kotamadya di provnsi Bengkulu dalamperiode 2007-2013, yang mana Random Effect Model (GLS) digunakan semagai teknik estimasi. Hasil penelitian menunjukkan bahwa belanja untuk pendidikan mempunyai pengaruh positf dan signifikan terhadap IPM, yang berartibahwa alokasi-alokasi anggaran substansial untuk pendidikan dapat memperbaiki IPM di provinsi Bengkulu. Disisi lain, belanja kesehatan dan belanja infrastruktur menunjukkan tidak signifikan dan mempunyai hubungan negatif diprovinsi Bengkulu. Selain itu, penelitian ini juga menemukan bahwa terdapat perbedaan yang signifikan tingkat IPM antara daerah utama dan daerah pemekaran, dimana daerah utama memiliki tingkat IPM yang lebih tinggi daripada daerah pemekaran.Key Words: Pendidikan, Belanja Pemerintah, HDI, Kesehatan, Infrastruktur.